Pengaruh kombinasi ekstrak etanol herba cecendet (Physalis angulata l.) dengan beberapa antibiotik terhadap bakteri Staphylococcus aureus dan Klebsiella pneumonie - Anna Choirunnisa; Afifah Bambang Sutjiatmo (Kartika : Jurnal Ilmiah Farmasi, 2017)
The effect of a combination of ethanol extract of Physalis angulata L. with antibiotic against Staphylococcus aureus and Klebsiella pneumonie                                                                                           Abstract Infectious disease is one of the biggest health problems not only in Indonesia, but worldwide. Bacteria are important agents in causing infectious diseases. Indonesian people often use antibiotics along with herbal medicines. Cecendet (Physalis angulata L.) is one of the traditional plants that have antibacterial activity and widely used by the Indonesian community. This study aims to test the antibacterial activity of cecendet herbs and their effects when used in combination with various antibiotics. The preparation of P.angulata extract was carried out using reflux method with ethanol 50%. The characteristic examination and phytochemical screening are examined on simplicia and the extract. Determination of antibacterial activity from P.angulata extract was done by microdilution test method by assessing minimum inhibitory concentration (MIC). Determination of the effectiveness of combination of antibiotics with herbal cecendet against test microbes Staphylococcus aureus and Klebsiella pneumoniae was done by using checkerboard method. The results of phytochemical screening showed that simplicia and P.angulata extract contained alkaloids, flavonoids, saponins, polyphenols, monoterpenoids, sesquiterpenes, steroids and triterpenoids. The result of antibacterial activity test showed that P.angulata extract had antibacterial activity against S.aureus and K.pneumoniae with the MIC was 128 μg/mL, 256 μg/mL. The synergistic interaction of S.aureus is demonstrated by the combination of P.angulata herb extract with tetracycline. The additive/indifferent interaction of S.aureus is demonstrated by the combination of P.angulata extracts with ampicillin, and against K.pneumoniae shown by the combination of P.angulata extract of cecendet with ampicillin or tetracycline. Ethanol extract of P.angulata has antibacterial activity and and combination with antibiotics (ampicillin/tetracyclin) can give synergistic effect or additive of S.aureus and K.pneumoniae bacteria. Keywords:  Cecendet, Physalis angulata L., MIC, antibiotic combination